Pembuatan Mesin Penyayat Kulit Hasil Samakan untuk Bahan Baku Sepatu - Rofarsyam Rofarsyam; Adi Putra (Faculty of Industrial Technology Universitas Islam Indonesia, 2005)
Domestic market of shoes is increasing. Howewer this opportunity is yet to be grasped by domestic producers. Lack of quality is of identified obstacles of the domestic products which are mostly produced by household industries to compete in the market. An aspect of the quality is product’s appearance that is influenced by quality of raw material which is leather. Hence, this recent research aims to design machine that can be used to yield better quality leather. In each 8 hours the machine can produce ready-to-used leather for 100 pairs of shoes.Keywords: leather, shoes.